1975
DOI: 10.3758/bf03209117
|View full text |Cite
|
Sign up to set email alerts
|

The influence of shock during response prevention upon resistance to extinction of an avoidance response

Abstract: A recent study found that avoidance extinction is equally facilitated by response prevention (blocking) whether the latter involves CS-alone or CS-shock presentations. An experiment was performed to determine whether this result was due to the use of a lengthy shock (5 sec) during response prevention. Five groups of rats were extinguished: (1) without prior blocking, (2) after blocking with CS only, (3) after blocking with a lengthy (5 sec) CS-contingent shock, (4) after blocking with a brief (.5 sec) CS-conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These low activity levels could indicate that freezing has become the "competing response." The Marrazo et al (1974) and Bersh and Miller (1975) experiments discussed previously certainly indicate that competing responses learned during flooding can mediate the extinction of avoidance responding. No experiment has conclusively demonstrated, however, that competing responses either do mediate extinction or are necessary for such extinction.…”
Section: Competing-response Theorymentioning
confidence: 92%
See 1 more Smart Citation
“…These low activity levels could indicate that freezing has become the "competing response." The Marrazo et al (1974) and Bersh and Miller (1975) experiments discussed previously certainly indicate that competing responses learned during flooding can mediate the extinction of avoidance responding. No experiment has conclusively demonstrated, however, that competing responses either do mediate extinction or are necessary for such extinction.…”
Section: Competing-response Theorymentioning
confidence: 92%
“…There are, however, two problems with this interpretation. First, Bersh and Miller (1975) showed that Marrazo et al's results were due to their use of long (S-sec) shocks during flooding. These long shocks seemed to result in jumping and rearing behavior being conditioned to the situation, which in turn facilitated extinction by serving as incompatible responses.…”
Section: Two-process Fear Extinction Theorymentioning
confidence: 99%
“…(2) Shock escape provides negative reinforcement for the response. When escape was unrestricted, the combination of these two factors increased extinction responding for CS-only animals to the level (i.e., 25-35 responses) consistently obtained for control rats (i.e., not exposed to response prevention) in our laboratory (e.g., Bersh & Miller, 1975;Bersh et aI., 1982), but not to the level of the CS-US animals. On the other hand, even 10 unrestricted escapes had no further reliable incremental effect on extinction responding for CS-US animals.…”
Section: Discussionmentioning
confidence: 95%